2005
DOI: 10.1212/01.wnl.0000156158.48587.ea
|View full text |Cite
|
Sign up to set email alerts
|

High-field, T2 reversed MRI of the hippocampus in transient global amnesia

Abstract: The data indicate that transient global amnesia may not be a benign entity. Delayed neuronal loss within CA1 area of Lorente de No may represent its important sequel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 30 publications
8
57
0
4
Order By: Relevance
“…66 Conversely, some conditions may present with stroke-like episodes and neurological symptoms that mimic CNS infarction (eg, mitochondrial encephalopathy, lactic acidosis, and stroke [MELAS], 67,68 posterior reversible encephalopathy syndrome, 69,70 and transient global amnesia). [71][72][73] However, although these conditions may have a component of ischemia, at this time, they are thought to have other primary mechanisms of cerebral damage and may be reversible without standard acute stroke therapies. The definition of CNS infarction may include atypical neurological symptoms when the symptoms are primarily attributed to focal (or multifocal) ischemia of the CNS.…”
Section: Definition Of Cns Infarction Should Include Neurological Conmentioning
confidence: 99%
“…66 Conversely, some conditions may present with stroke-like episodes and neurological symptoms that mimic CNS infarction (eg, mitochondrial encephalopathy, lactic acidosis, and stroke [MELAS], 67,68 posterior reversible encephalopathy syndrome, 69,70 and transient global amnesia). [71][72][73] However, although these conditions may have a component of ischemia, at this time, they are thought to have other primary mechanisms of cerebral damage and may be reversible without standard acute stroke therapies. The definition of CNS infarction may include atypical neurological symptoms when the symptoms are primarily attributed to focal (or multifocal) ischemia of the CNS.…”
Section: Definition Of Cns Infarction Should Include Neurological Conmentioning
confidence: 99%
“…21 Whatever its etiology, several authors have suggested that delayed neuronal injury in the hippocampus is the cause of the delayed appearance of the lesions on DWI. 9,22 It has also been speculated that delayed lesion appearance could be a result of progressive T2 prolongation of the lesions with time, as observed for thromboembolic infarctions. 12 This speculation arises from the finding that small acute infarctions in the basal ganglia frequently have greater DWI signal intensities on the second or third days than on the first day post-symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…9 There have been recent reports of the use of high-resolution T2 reversed MRI in obtaining detailed anatomy of fine structures in humans. 13 Some investigators have used diffusion-weighted imaging to examine the etiology of TGA, but the results have been controversial. 14 Several conditions have been reported to precipitate TGA: physical exertion, emotional stress, sexual intercourse, swimming in cold water, 1 coronary angiogra- 18 and reactivation of Epstein-Barr virus infection.…”
Section: Discussionmentioning
confidence: 99%